Professionals' reports on intercurrences in aesthetic body treatments (Research, Society and Development, 2021)
The search for aesthetic treatments has increased considerably in recent times regardless of age and gender, the objective is the perfect body, without stretch marks, cellulite, and localized fat. The objective of this study was to identify what are the complications of aesthetic body treatments. The study is characterized as descriptive with a quantitative approach. Due to the situation of COVID -19, the study was conducted in a non face-to-face manner, through a questionnaire on Google Forms. The research was carried out with 28 health professionals such as aestheticians, physical therapists, nurses and biomedical professionals working in the field of body aesthetics. It was possible to identify the complications in body aesthetic treatments that range from the simplest to the most complex such as burns, stains and paradoxical hyperplasia. It was also observed the therapeutic resources that presented the most complications and the main behaviors that the professionals had when facing these complications. The theme is very important nowadays, but few publications can be found, which is extremely relevant for health professionals who work with body esthetics.